THE CONTINGENCY CONTRACT IN THE HUNGARIAN LAW - Máté, Mohai (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The new Hungarian Civil Code - similarly to the Vienna Convention and the Principles of European Contract Law – regulates the so called contingency contract. A contingency contract is a special way of calculating damages. A contract is a contingency contract if the obligee replaces a quantity of goods not performed to him due to the debtor's breach of contract. The obligee may enter into a contingency contract in the event of the impossibility or withholding of performance or in the event of a delay giving rise to a right of termination. Contingency contracts are concluded either for purchase or for sale.